Biology in science teaching periodicals: an analysis of theoretical trends (Research, Society and Development, 2020)
This paper aimed to identify and analyze how much of biology is present in science teaching periodicals, and what the theoretical trends of these researches are. Initially, we selected Science Teaching and Education journals that had the term biology teaching in their scope, resulting in nine journals. From these, articles published in 2018, which deal with the teaching of Biology, were selected. The analysis of the theoretical trends of the articles was characterized by descriptors, supported by the state of the art methodology, including privileged content area, school level, and thematic focus of the research. We found a higher prevalence of General Biology research, followed by Environmental Education and the Environment. We also identified a concentration of research in high school and higher education, and thematic focus on the content-method relationship, followed by teacher education. It is noteworthy that works of this nature are indispensable because they allow an overview of the academic production of research in the teaching of Biology, in order to promote the dissemination of scientific research of thematic focuses, as well as verify gaps and new research demands in specific areas, less explored in its teaching and learning process.